ANALISIS PENERAPAN PERANGKAT LUNAK AKUNTANSI: STUDI KASUS PADA USAHA JASA SKALA MENENGAH - Palupi, Ade; Sayidina Az Zahra, Mirza; Jumansyah; Yolanda, Desva (Universitas Kristen Krida Wacana, 2025)
This study aims to analyze the effectiveness of accounting software usage in medium-scale service companies and to identify the factors that influence the success of its implementation. The study employs a qualitative method with a case study approach involving three service companies located in the DKI Jakarta. Data were collected through in-depth interviews with financial managers and accounting staff, as well as observations of financial recording and reporting processes conducted using accounting software. The results indicate that the effectiveness of accounting software is influenced by users’ foundational accounting knowledge, work experience, information technology skills, training, and organizational support. Accounting software provides several significant benefits, including faster financial reporting, reduced human error, easier tax calculations, operational process efficiency, and improved accuracy in financial analysis and internal control. Nevertheless, the study identifies several challenges, such as high investment and maintenance costs, dependence on service providers when errors occur, and the need for periodic hardware upgrades. The value of this study is it highlights that accounting software serves as an essential component of accounting information systems, capable of enhancing the accuracy, efficiency, and timeliness of financial reporting in medium-scale service companies, provided that it is supported by competent human resources, adequate training, and technological readiness. The limitations of this study include its narrow geographic scope, limited number of informants, and data characteristics that rely heavily on respondents’ subjective perceptions. Keywords: accounting software, accounting information systems, medium-scale service companies, service enterprise